Molecular characterization of Neospora caninum major antigens NcSAG1 and NcSRS2 - Soledad Echeverría; Federico Carrión; Martín Soñora; Andrés Cabrera; Carlos Robello (Royal Society Open Science)
The SAG1-related sequence (SRS) protein family was initially identified in Toxoplasma gondii as glycosyl-phosphatidylinositol-anchored surface antigens. More recently, they have been identified in Neospora caninum, the causative agent of neosporosis, a leading cause of bovine abortion worldwide. These proteins are implicated in parasite adhesion to and invasion of host cells, immune response modulation and structural roles in the cyst wall. In this study, we characterized two key N. caninum SRS proteins, NcSAG1 and NcSRS2, through sequence analysis, structural modelling, biophysical characterization and immunochemical assessment. Sequence analyses revealed conserved domains, including hallmark D1 and D2 regions, but with significant sequence divergence. Using AlphaFold, we constructed reliable structural models, confirming conserved features such as disulfide bond patterns and dimerization. Structural comparisons demonstrated a high degree of conservation within D1 domains despite low sequence similarity. Recombinant NcSAG1 and NcSRS2 were expressed as soluble and stable proteins in Drosophila melanogaster S2 cells, achieving yields comparable to the most efficient prokaryote expression systems. Size exclusion chromatography and dynamic light scattering demonstrated their dimeric nature and structural stability, with melting temperatures exceeding 50°C. Circular dichroism spectroscopy confirmed their correct secondary structure content, validating proper folding and structural integrity. Antigenicity assays demonstrated universal recognition by sera from experimentally and naturally infected hosts, highlighting their potential as diagnostic markers or vaccine candidates. Comparative structural analysis of 219 SRS family members, based on sequence and AlphaFold-predicted structures, revealed conserved cysteine, proline and tryptophan motifs. Hierarchical clustering and phylogenetic analyses identified key evolutionary clusters, correlating structural divergence with functional specialization. Discrepancies between sequence- and structure-based trees underscored instances of structural evolution not reflected in sequence data. This comprehensive analysis bridges sequence divergence, structural conservation and biological function, providing a robust framework for investigating SRS proteins’ roles in pathogenesis and immunity. Our findings lay the groundwork for future research into N. caninum’s molecular mechanisms and their implications for controlling neosporosis.